BRICS Expansion: A Geopolitical Triumph of Partner Countries - V. Gavrilenko; V. Shenshin (BRICS Law Journal)
The BRICS organization is making significant and consistent progress in its development. The 15th BRICS Summit was held in Johannesburg from 22 to 24 August 2023. This summit is a global event that sets the trends and guiding principles for future economic policies. Four of the five BRICS member countries are among the ten largest countries in the world in terms of GDP, territory and population. According to open sources, the total area of the BRICS countries is 39.7 million square kilometers (26.7% of the world’s land surface), and the population is estimated at3.2 billion people (41.5% of the world’s population). The economic potential of BRICS, as the leading economic organization in the world, is more than significant. These competitive advantages in the economy and financial sphere represent an enormous resource of industrial, human and technological potential that can serve as the locomotive of the global economy. Following the conclusion of the above summit, the leaders of the BRICS countries adopted the final “Johannesburg-2” declaration, which noted the advisability of using their countries’ respective national currencies in international trade and collectively resolving problems related to international debt. In addition, decisions were made to expand BRICS and admit new member states to the organization. BRICS has established itself as a prominent entity on the global stage, whose influence in world affairs is consistently strengthening. The strategic course of their unification is aimed at planning for the future and meets the interests of the leading nations of the international community, the so-called world majority. By acting cohesively on the principles of equality, partnership support and mutual consideration, the BRICS member countries are effectively addressing the most pressing issues on the global and regional agenda. The BRICS member states are strongly in favor of the establishment of a multipolar world order that is based on international law and is fair. At the same time, they are committed to adhering to the fundamental principles of the United Nations Charter. BRICS is the most important guarantor of the legal foundations of international relations and a fair world order in general. The recent expansion of the BRICS group is a significant event that enables the group to have an even greater influence in international affairs. The presented article analyzes the features of the recent expansion of BRICS and its impact on world geopolitics, taking into account the admission of new states to the organization. The distinctive features of the BRICS group activities and its role in relation to the G7 and G20 are revealed. The trends in the transition to a multipolar world are discussed. Furthermore, issues of political and economic cooperation between the different BRICS member countries are analyzed.